UPAYA INGGRIS DALAM MENJAGA HUBUNGAN PEREKONOMIAN DENGAN INDIA PASCA REFERENDUM BREXIT - Radha Khrisnanta, Putu Gede; Kumala Dewi, Putu Ratih; Widya Nugraha, AA Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT Brexit Referendum gives impact to foreign direct investment from India’s big companies in United Kingdom that shown their reaction about United Kingdom decision. This research aims to explain any efforts by United Kingdom in order to keep their economic relations with India, especially on investment sector after Brexit Referendum. Those United Kingdom’s efforts are materialized into some policies that aims to keep investment from India’s companies not decreasing in number after Brexit Referendum. The data in this research was analyzed by using descriptive qualitative methods with secondary data resource and the concept of Economic Statecraft, especially with positive Economic Statecraft’s instruments. This research perceives that United Kingdom’s efforts that are materialized into government policies aims to keep up the economic relations with India, especially for India’s investment in United Kingdom after Brexit Referendum with the application of positive Economic Statecraft’s instruments. Keywords: Brexit Referendum, economic statecraft, foreign direct investment